2012
DOI: 10.1007/s13365-012-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Catechins protect neurons against mitochondrial toxins and HIV proteins via activation of the BDNF pathway

Abstract: Currently, there is no effective treatment for neurological complications of infection with the human immunodeficiency virus that persists despite the use of combination antiretroviral therapy. A medium throughput assay was developed for screening neuroprotective compounds using primary mixed neuronal cells and mitochondrial toxin 3-nitropropionic acid. Using this assay, a library of 2,000 compounds was screened. Out of 256 compounds that showed variable degrees of neuroprotection, nine were related to epicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…Considerable experimental data indicate that the HIV-1 exterior envelope glycoprotein gp120 (HIV-1 gp120), which is shed from the virus, can cause neurotoxicity by multiple mechanisms (Nath et al 2012). Out recent study found that HIV-1 gp120 in postmortem tissues of the spinal cord dorsal horn was significantly higher in the pain-positive HIV-1 patients, compared to the pain-negative HIV-1 patients (Yuan et al 2014).…”
Section: Instructionmentioning
confidence: 99%
“…Considerable experimental data indicate that the HIV-1 exterior envelope glycoprotein gp120 (HIV-1 gp120), which is shed from the virus, can cause neurotoxicity by multiple mechanisms (Nath et al 2012). Out recent study found that HIV-1 gp120 in postmortem tissues of the spinal cord dorsal horn was significantly higher in the pain-positive HIV-1 patients, compared to the pain-negative HIV-1 patients (Yuan et al 2014).…”
Section: Instructionmentioning
confidence: 99%
“…Curcumin treatment also reduced neuronal and microvessel degeneration in the retina in a rat model of ischemiareperfusion injury (Wang et al, 2011c). Catechins protected cultured neurons against death induced by the mitochondrial toxin 3-nitropropionic acid (3NP) (Nath et al, 2012). Administration of luteolin to rats for 13 days beginning immediately after experimental stroke resulted in increased survival of neurons in the ischemic cerebral cortex and improved functional outcome .…”
Section: B Metabolic Stressmentioning
confidence: 99%
“…Epicatchins have been found to have broad neuroprotective actions against oxidative and metabolic stress in experimental models relevant to the pathogenesis of stroke, Alzheimer's and Parkinson's diseases, and HIV dementia (Sutherland et al, 2006;Lin et al, 2009;Schroeder et al, 2009;Nath et al, 2012). Studies of cultured neural cells suggest that the underlying mechanisms involve activation of the PI3 kinase -Akt pathways and stimulation of BDNF production (Jang et al, 2010;Nath et al, 2012). Epicatechins may also reduce the risk of cardiovascular disease by lowering levels of pro-atherosclerotic lipids and reducing blood pressure (Moore et al, 2009;Ellam and Williamson, 2013).…”
Section: Challenge 3: Noxious Dietary Phytochemicalsmentioning
confidence: 99%